Adsorption Study Of Heavy Metals And Natural Organic Matters (Nom) In Groundwater Using Metakaolin - Sapingi, Mohd Sharizal Mohd (2019)
Groundwater is an increasingly important source of water due to lack of surface water supply that caused by climates vagaries and declined surface water quality. However, prior to consumption, it is very essential to recognize the quality of groundwater to avoid adverse effect to health as the quality differs based on location. Elevated heavy metals concentrations in groundwater are one of the common issues due to the anoxic and reductive condition in groundwater. In addition, high natural organic matter (NOM) content in groundwater decrease the water aesthetic value and develop disinfection by-product when reacted with disinfectant. Therefore, the objectives of this study are; 1) To study the quality of groundwater sampled; 2) to explore capability of metakaolin in order to reduce the contaminant (iron, manganese, nickel and NOM) concentration in groundwater and the factors (dosage, agitation rate & contact time) optimization using RSM; and 3) to determine the suitable isotherm and kinetics behavior for each contaminant. . In average, the concentration of the contaminant is high with iron (615.4 μg/L), manganese (444.0 μg/L), nickel (174.6 μg/L) and NOM (as measured in UV254)(1.23 cm-1). The optimum setting (dosage, agitation rate and contact time) was assessed using RSM where the removal of iron, manganese, nickel and NOM was 82%, 38%, 39% and 22% respectively. High ionic strength and competitive adsorption in a multi-solute system have been recognized as limiting factors. Isotherm study signified that the adsorption of all contaminants onto metakaolin fits with the Freundlich model as the values of 1⁄